Lessons from the COVID-19 pandemic for substance misuse services: findings from a peer-led study - Katy Holloway; Shannon Murray; Marian Buhociu; Alisha Arthur; Rondine Molinaro; Sian Chicken; Elwyn Thomas; Sam Courtney; Alan Spencer; Rachel Wood; Ryan Rees; Stephen Walder; et al. (BMC, 2022)
Abstract Background The measures implemented to contain the spread of the COVID-19 virus disrupted the provision of substance misuse treatment and support. However, little is known about the impact of this disruption on individuals seeking treatment for drug- and/or alcohol-related problems (henceforth service users). This study aimed to help substance misuse services learn lessons and identify ways of optimising delivery and minimising harm in the event of any future lockdowns or global crises. Methods The study was co-produced by a team of peer researchers, practitioners, policymakers and academics. Telephone interviews were conducted with 202 substance misuse service users over a 6-month period commencing June 2020. The interviews were conducted by a small group of seven peer researchers each with lived experience of substance use problems. The interview data were recorded by the peers in an anonymous online questionnaire survey and analysed using standard quantitative and qualitative methods. Results Service users responded to the COVID-19 pandemic in a variety of ways. Diverse responses were noted in relation to their substance use patterns, their personal lives and their substance misuse treatment experiences. For some, the pandemic acted as a new risk environment factor that increased their vulnerability to substance-related harm. For others, it facilitated aspects of the enabling environment, thereby reducing the risk of harm. Conclusions Service users are not a homogenous group, and an individualised approach to treatment that recognises the potential for varied responses to the same stimuli is needed. The findings suggest that service users would benefit from having a choice in how they access treatment and from greater access to outreach programmes that take treatments and harm reduction tools such as naloxone into the community. The research also supports the involvement of people with lived experience in substance use research, policy and practice.